Cameron lesions in patients with hiatal hernias: prevalence, presentation, and treatment outcome. Issue 5 (24th April 2014) - Gray, D. M.; Kushnir, V.; Kalra, G.; Rosenstock, A.; Alsakka, M. A.; Patel, A.; Sayuk, G.; Gyawali, C. P.
Summary Cameron lesions, as defined by erosions and ulcerations at the diaphragmatic hiatus, are found in the setting of gastrointestinal (GI) bleeding in patients with a hiatus hernia (HH). The study aim was to determine the epidemiology and clinical manifestations of Cameron lesions. We performed a retrospective cohort study evaluating consecutive patients undergoing upper endoscopy over a 2‐year period. Endoscopy reports were systematically reviewed to determine the presence or absence of Cameron lesions and HH. Inpatient and outpatient records were reviewed to determine prevalence, risk factors, and outcome of medical treatment of Cameron lesions. Of 8260 upper endoscopic examinations, 1306 (20.2%) reported an HH. When categorized by size, 65.6% of HH were small (<3 cm), 23.0% moderate (3–4.9 cm), and 11.4% were large (≥5 cm). Of these, 43 patients (mean age 65.2 years, 49% female) had Cameron lesions, with a prevalence of 3.3% in the presence of HH. Prevalence was highest with large HH (12.8%). On univariate analysis, large HH, frequent non‐steroidal anti‐inflammatory drug (NSAID) use, GI bleeding (both occult and overt), and nadir hemoglobin level were significantly greater with Cameron lesions compared with HH without Cameron lesions (P ≤ 0.03). Large HH size and NSAID use were identified as independent risk factors for Cameron lesions on multivariate logistic regression analysis. Cameron lesions are more prevalent in the setting of large HH and NSAID use, can be associated with GI bleeding, and can respond to medical management.